Clot penetration and fibrin binding of amediplase, a chimeric plasminogen activator (K2tu-PA) - Rijken, Dingeman C.; Barrett-Bergshoeff, Marrie M.; Jie, A. F. H.; Criscuoli, Marco; Sakharov, Dmitri V. (Thrombosis and Haemostasis, 2004)
Amediplase (K2tu-PA) is a hybrid plasminogen activator, consisting of the kringle 2 domain of alteplase and the protease domain of urokinase. The objective of this study was to determine the in vitro clot penetration of amediplase in relation to its fibrin binding and to compare the properties with those of alteplase.The clot lysis activity of amediplase in internal clot lysis models (both purified system and plasma system) was about 10 times less than that of alteplase. The clot lysis activity of amediplase in an external clot lysis model (plasma system) was similar to that of alteplase at therapeutic concentrations around 1 µg/ml. The fibrin-clot binding properties of amediplase and alteplase were studied in a purified system as well as in a plasma system. In both systems amediplase bound to fibrin although to a significantly lower extent than alteplase. The binding of amediplase or alteplase did not increase during plasmin-mediated degradation of fibrin. The binding of amediplase was fully inhibited by epsilon-aminocaproic acid, indicating that the observed binding was specific and occurred via the lysine binding site in the kringle of amediplase. Clot penetration was studied during pressure-driven fluid permeation using syringes containing plasma clots. Amediplase was able to enter the clot without significant hindrance, while alteplase was concentrated on the top of the plasma clot and hardly entered into the inner parts of the clot. Diffusion-driven clot penetration was studied during clot lysis using confocal microscopy. Alteplase was detected on or close to the clot surface, while two-chain urokinase, which has no affinity to fibrin, was also detected deep inside the clot. Amediplase showed a penetration behaviour, which was distinct from that of alteplase and similar to that of two-chain urokinase.We concluded that the fibrin binding of amediplase is moderate and does not hinder clot penetration under permeationdriven or diffusion-driven transport conditions. Enhanced clot penetration, especially in large clots, could allow a more efficient lysis during thrombolytic therapy.
Keywords: Amediplase; alteplase; fibrin binding; clot penetration; thrombolysis